2020
DOI: 10.1038/s41598-020-59192-z
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Case of Langerhans Cell Histiocytosis in a Cretaceous dinosaur

Abstract: Susceptibility to diseases is common to humans and dinosaurs. Since much of the biological history of every living creature is shaped by its diseases, recognizing them in fossilized bone can furnish us with important information on dinosaurs' physiology and anatomy, as well as on their daily activities and surrounding environment. In the present study, we examined the vertebrae of two humans from skeletal collections with Langerhans Cell Histiocytosis (LCH), a benign osteolytic tumor-like disorder involving ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 65 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…Neoplastic disease is rare in vertebrate fossils [ 58 , 59 , 61 ], also few metabolic disorders have been described, such as Paget’s disease or gout [ 58 ]. Other authors, suggested that pathological processes are independent of phylogeny and time [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic disease is rare in vertebrate fossils [ 58 , 59 , 61 ], also few metabolic disorders have been described, such as Paget’s disease or gout [ 58 ]. Other authors, suggested that pathological processes are independent of phylogeny and time [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Full features resulting from Langerhans Cell Histiocytosis inferred in other hadrosaurids, based on its smooth margin and "wrinkled" internal surface (Rothschild et al, 2020). However, it is intuitively implausible that an osteologically borne disease instigated the mass mortality event.…”
Section: Taphonomy Of the Spring Creek Bonebedmentioning
confidence: 99%
“…Even the classic alteration found in some individuals with gout can also be found with amyloidosis and multicentric reticulohistiocytosis (Resnick, 2002;Rothschild, 1982). There are exceptions (e.g., diarthrodial joint osteophytes identifying osteoarthritis, Altman et al, 1986Altman et al, , 1990Altman et al, , 1991 and crenulated changes identifying Langerhans cell histiocytosis (Rothschild et al, 2020)].…”
Section: Shared Disease Characteristicsmentioning
confidence: 99%